2013
DOI: 10.1117/1.oe.52.7.076101
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked 2-μm wavelength fiber laser using a graphene-saturable absorber

Abstract: Abstract. Soliton-like pulses with a 1984-nm center wavelength are produced from a Tm-doped mode-locked fiber laser. The linear cavity has a graphene saturable absorber mirror at one end and a fiber Bragg grating as the output coupler. The laser operates without dispersion compensation, and the repetition rate was tuned from 20 to 5 MHz by the addition of SMF-28 fiber. The dry transfer process used to place the graphene on a mirror could be extended to any optical substrate. This enables integration of graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As discussed earlier in Section 18.7.2, the ambient is thought to be the source of the p-type dopant [109]. Using multilayer graphene transferred from C-face samples to an optical element, Currie demonstrated promising performance of the first saturable absorber laser operation at 2 mm using EG [117]. It was concluded that Bernal-stacked bilayer graphene inclusions were present, as these would give rise to the linear B behavior [116].…”
Section: Growth On C-face Using Argon Blanket Gas and Confined Synthementioning
confidence: 95%
“…As discussed earlier in Section 18.7.2, the ambient is thought to be the source of the p-type dopant [109]. Using multilayer graphene transferred from C-face samples to an optical element, Currie demonstrated promising performance of the first saturable absorber laser operation at 2 mm using EG [117]. It was concluded that Bernal-stacked bilayer graphene inclusions were present, as these would give rise to the linear B behavior [116].…”
Section: Growth On C-face Using Argon Blanket Gas and Confined Synthementioning
confidence: 95%
“…38 Moreover, our results for the parabolic shape of the pulse and the behavior of the laser pulse propagation through the fiber laser exhibit good agreement with previous studies. [39][40][41][42][43] …”
Section: Discussionmentioning
confidence: 99%